Investigation of the interplay of PCSK9, cardiac dynamics, oxidative stress in coronary artery disease: case-control study - Lafta, Anmar Hussein; Shiri, Hamidreza; Iraji, Mahsa; Karimpour, Amin; Sattari, Mahboobe; Rahimkhani, Monireh; Einollahi, Nahid; Panahi, Ghodratollah (Frontiers in Endocrinology, 2025)
BackgroundPCSK9 plays a key role in raising LDL-C levels, which contributes to heart attacks (MI). However, studies show that about half of MI patients have normal LDL-C levels. This study aims to explore the link between PCSK9, heart function, and oxidative stress markers in MI patients.MethodsThis investigation was carried out at Tehran Heart Centre Hospital on healthy individuals (n=63) and patients (n=63) with MI who had a coronary artery block above 50% (CAB > 50%). Oxidative stress (OS) parameters, such as total antioxidant capacity (TAC), malondialdehyde (MDA), myeloperoxidase (MPO), superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) activity, PCSK9, oxidized Low-density lipoprotein (ox-LDL), high-sensitivity cardiac troponin I (hs-cTnI), and hs-CRP are assessed. Indeed, biochemical parameters and EF% were measured.ResultsHigher EF% (>37.5%), TAC (>1.05 mmol Fe²+;/L), GPx (>16.48 mU/mL), CAT (>11.32 nmol/min/mL), and SOD (>297.16 U/mL) were linked to a lower risk of CAB > 50%. In contrast, higher MDA (>32.07 nmol/mL), MPO (>17.77 U/L), hs-CRP (>5.5 mg/L), and ox-LDL (>64.87 μg/L) were associated with a higher risk. There was no significant difference in PCSK9 and LDL-C levels between groups. EF% was positively linked to SOD but negatively related to MDA, MPO, ox-LDL, hs-cTnI, and hs-CRP. Ox-LDL correlated positively with MPO but negatively with TAC, CAT, and GPx. PCSK9 showed a positive relationship with MDA. The best markers for CAB > 50% diagnosis were ox-LDL (AUC = 83.22, cut-off > 63.35 μg/L), EF% (AUC = 82.35, cut-off < 46.25%), and hs-cTnI (AUC = 81.3, cut-off > 0.265 ng/mL).ConclusionWhile PCSK9’s role in MI through LDL-C is well known, its impact on inflammation and oxidative stress may also be important, even when LDL-C and PCSK9 levels are normal. Additionally, ox-LDL and EF% are better indicators of CAB > 50% than hs-cTnI.